Membangun Karakter Anak: Peduli Sesama, Hemat, dan Lestarikan Tradisi di SDN 003 Tarakan - Nurul Hidayat; Anggun Sarwana; Maya Nur Melisah; Siska Sonya Nanda Dewi; Siti Jubaidah; Rehan Aldi Saputro; Marwan Zaesar Gabstan (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2025)
This community service activity was carried out at SDN 003 Tarakan with the aim of instilling character values in grade 5 students, especially the values of caring for others, living frugally, and preserving local traditions. This program is designed as an effort to strengthen character education through an interactive, fun, and relevant approach to students' daily lives. The implementation method includes delivering material through interactive presentations, group discussions, and educational games designed to encourage active participation and contextual understanding. The results of the activity showed the high enthusiasm of the students, as seen from their involvement in the question and answer session, the activeness of participating in mini games, and the ability to connect the material with personal experiences. In addition, students show increased awareness of the importance of caring, frugal behavior, and love for local traditions. This activity not only provides conceptual understanding, but also encourages students to apply character values in real actions in the school and home environment. Overall, this service program contributes to the formation of a young generation that cares, is independent, and has a commitment to the preservation of local culture.